Formulasi Perancangan Strategi Pengembangan Usaha Pada Avelina Parfum - Subiya, Atika Triya; Wijaya, Fanji (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to formulate a business development strategy for Avelina Parfume using SWOT and Business Model Canvas analysis approaches. The strengths, weaknesses, opportunities, and threats faced by Aveline Parfums are identified and analyzed in depth through a SWOT evaluation. The research methods used are descriptive qualitative methods. Primary data was collected through direct interviews with owners, employees, and consumers of Avelina Parfume. Secondary data is obtained from documents and literature on business development strategy at UMKM in the perfume industry. The company's strengths are product quality and brand image, while its weakness is dependence on a single supplier. Opportunities include increased awareness of local perfumes and online markets, with major threats coming from tight competition and changing consumer preferences. Based on the analysis, a new Business Model Canvas is recommended to improve competitiveness and growth potential. Improvement recommendations include diversification of suppliers, enhanced digital marketing, and product innovation according to consumer preferences. This strategy is expected to improve the sustainability of Avelina's business